Underexploited Vegetables of Northeastern Region - Dubey, Rakesh Kumar; Singh, Vikas; Pandey, Sudhakar (Indian Horticulture, 2024)
Underexploited plant species cover an enormous range of plants that have the potential to contribute to nutritional and livelihood security. Northeastern region of the country is blessed with varied climatic conditions which provides habitat to a number of green foods, some of which are still underexploited and their knowledge is confined to some tribal and ethnic communities living in close conformity to the nature. Many of these plant species are found resilient, adaptive and tolerant to adverse climatic conditions. They have remained underexploited due to the lack of awareness and popularization techniques for utilization. There is an increasing interest and demand for indigenous underexploited vegetables reflecting a growing trend within agriculture to identify and develop new crops which are often referred to as neglected and underutilized species. Northeast region has immense potential to claim as the horticultural hub of the country as the agro-climate here favours the growth of many major and underexploited vegetable crops. To harness the full potential of the region, robust strategies coupled with scientific interventions are in need.